45.3k views
3 votes
Solve for n. Make sure to show all your work. 6(-6n-6)-7=-331

User Maumercado
by
5.6k points

2 Answers

3 votes

Answer:

n=8

Explanation:

Step 1: Simplify both sides of the equation.

6(−6n−6)−7=−331

(6)(−6n)+(6)(−6)+−7=−331(Distribute)

−36n+−36+−7=−331

(−36n)+(−36+−7)=−331(Combine Like Terms)

−36n+−43=−331

−36n−43=−331

Step 2: Add 43 to both sides.

−36n−43+43=−331+43

−36n=−288

Step 3: Divide both sides by -36.

−36n−36=−288−36

n=8

User Lightxbulb
by
6.4k points
3 votes
N=-8
Hope this helps
Solve for n. Make sure to show all your work. 6(-6n-6)-7=-331-example-1
User Pankaj Agrawal
by
6.0k points